PERANAN BAJRA SANDHI SEBAGAI OBJEK WISATA PADA DENPASAR CITY’S TOUR ITINERARY - I Gede Kutiana Anantaya (Jurnal Ilmiah Hospitality Management, 2012)
Bajra Sandhi Monument was built in 1987 and inaugurated in 2003 by Megawati Sukarno Putri, Indonesian Republic President.  The name of Bajra Sandi is taken from the form of building, it’s a bell of Hindu’s priest which used to complete the mantram when the priest carry out the ceremony. It’s an attractive tourist attraction located in the centre of Denpasar city as a place of historical tourism product of Balinese history. The aim of this research is to find out the role of Bajra Sandhi as tourist attraction in Denpasar City’s Tour Itinerary. The research was conduct by applying descriptive qualitative analysis approach. In this research involve 26 samples, the students of Tour and Tourism, Diploma III, Tourism Department, Bali State Polytechnic. Data were obtained through two type of instruments such as; questionnaire and document. The result of the research were: 0.58 of samples/students said strongly agree that Bajra Sandhi as an interesting historical tourism product, 0.71 of samples/students said strongly agree that Bajra Sandhi as tourism product of character building, which is able to build rhe character of visitors/tourists commonly and Balinese specifically, and 0.64 of samples/students said strongly agree that Bajra Sandhi as suitable choice for a destination point put it on in Denpasar City’s Tour Itinerary.